Are Medıcal Students Famılıar Wıth Patıent Safety Culture? A Cross-Sectıonal Study in Turkey - Yasemin Aslan; Orhan Zengin; Ayşegül Karaca Dedeoğlu; Cenk Hilmi Kılıç (Asia Pacific Journal of Health Management)
Background: Patient safety is a key indicator of healthcare quality. The purpose of this study is to evaluate the attitudes of medical students towards patient safety culture.